A critical insight into the development, regulation and future prospects of biofuels in Canada. Issue 2 (20th December 2021) - Saini, Rahul; Osorio-Gonzalez, Carlos Saul; Brar, Satinder Kaur; Kwong, Raymond
ABSTRACT: Renewable biofuel has a great potential in replacing the conventional transportation fuels as well as aiding the current issue of climate change and global warming. In the present scenario, tremendous initiatives have been implemented to encourage large-scale biofuel production and reduce greenhouse gas emissions. However, the information on the current biofuel status specifically in Canada and where it lacks in biofuel production, tax rebate and policies in comparison with other countries is limited. In this sense, the current work focuses on the liquid biofuel status, recent advancements and evaluation of programs aimed at reducing greenhouse gas emissions in coming years. Additionally, the role of private and government programs in scaling up the projects is elaborated using several examples of successful as well as failed attempts to commercialize biofuels. Moreover, the Canadian government regulations and policies for greenhouse gas mitigation, and biofuel blending policies are also briefly described. In summary, future aspects and suggestions to further increase biofuel production are portrayed in this review.